Value of Serum Carbohydrate Antigen 19-9 and Carcinoembryonic Antigen in Evaluating Severity and Prognosis of Connective Tissue Disease-Associated Interstitial Lung Disease - Qian JIN; Jisheng ZHENG; Xianrong XU; Yeming HU; Ying ZHOU; Weihua XU; Feihua HUANG (Archives of Rheumatology, 2018)
Objectives: This study aims to detect serum carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA 19-9) levels in connective tissue disease-associated interstitial lung disease (CTD-ILD) patients and to demonstrate their values in evaluating the severity and prognosis of CTD-ILD. Patients and methods: The study included 82 CTD-ILD patients (54 males, 28 females; mean age 67.9 years; range 29 to 91 years) and 82 controls (54 males, 28 females; mean age 68.1 years; range 30 to 92 years). Patients were followed-up for 12 months. Correlations of serum CEA and CA 19-9 with disease severity parameters (pulmonary function, oxygenation index and involvement score on high resolution computed tomography) were analyzed. Survival analysis was used to evaluate significance of serum CEA and CA 19-9 as prognosis predictors. Results: Serum CEA and CA 19-9 levels were higher in CTD-ILD patients compared with controls (both p<0.05) and correlated with disease severity (p<0.05 for all R2). High levels of serum CEA and CA 19-9 were associated with poor survival (both p<0.05). Serum CEA level was indicated as a prognostic factor for cumulative survival (hazard ratio=1.685, 95% confidence interval: 1.405-2.021, p=0.001). Conclusion: In CTD-ILD patients, serum CEA and CA 19-9 are elevated and can be indicators of disease severity. Moreover, serum CEA is a significant and independent predictor of survival.